EMBRIOGENESIS SOMATIK ROTAN TOHITI (Calamus inops Becc. ex Heyne) - Yelnititis Yelnititis (Jurnal Pemuliaan Tanaman Hutan, 2018)
The conventional propagation of tohiti rattan still faces problem because of infrequent fruiting season and limited seed production. Somatic embryogenesis is an alternative technique to solve the problem. The purpose of this experiment is to obtain the best growth regulator treatments for embryogenic callus and somatic embryo formation of tohiti rattan. Murashige and Skoog (MS) basal medium was used as growth medium. The experiment was conducted in three stages: seed germination, embriogenic callus induction and somatic embryo induction. MS medium without plant growth regulator was used for aseptic seed germination. MS medium supplemented with growth regulator of BA (Benzyl adenine) of 0.5 – 2.0 mg/l was used for embryogenic callus induction. MS medium supplemented with BA 1.0 mg/l in combination with hormone 2.4-D of 0.0 – 1.0 mg/l was used for somatic embryo induction. The seed germination percentage, visual performance on embryogenic callus and somatic embryo were observed. The results showed that the percentage of aseptically seed germination reached 90%. MS medium supplemented with 1.0 mg/l BA is the best media for embryogenic callus induction with friable, white and yellowish of callus which was observed after four months of induction culture. The BA of 1.0 mg/l in combination with 2.4-D of 1.0 mg/l provided the highest number of the formed somatic embryo.The performance of somatic embryos formation from this treatment was likely as zygotic embryo.